Features of soil treatment and systems of fertilizing chernozem leached during crop rotation - N. I. Devterova (Новые технологии, 2017)
As a result of many years of research, the influence of various fertilizer systems and soil treatment methods on the main indicators of soil fertility of chernozem leached in crop rotation was revealed. The use of organic optimal and organomineral enhanced fertilizer systems combined with minimizing soil processing in crop rotation ensured an increase in the humus content for all the layers studied, on average from 0.1 to 0.5%.